2016
DOI: 10.1177/2042098616667704
|View full text |Cite
|
Sign up to set email alerts
|

Rifampicin and isoniazid plasma concentrations in relation to adverse reactions in tuberculosis patients: a retrospective analysis

Abstract: Objective: High concentrations of antituberculosis (anti-TB) drugs can be associated with many adverse drug reactions (ADRs). The objective of this study was to examine the plasma concentrations of rifampicin (RMP) and isoniazid (INH) in patients with and without ADRs. Methods: Concentration monitoring data of patients treated with anti-TB drugs were retrospectively analyzed from 2009 to 2011. RMP and INH plasma concentrations were measured 2 and 3 h after drug administration respectively using high-performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
(37 reference statements)
1
7
0
Order By: Relevance
“…Indeed, a significant correlation would guide the clinician to prescribe a dose corresponding to the desired target concentration. This corroborates the results of a retrospective analysis performed by Moussa et al, 27 who found no correlation between isoniazid C 3 and weight dose in both patients having and patients not having adverse drug reactions ( r = 0.22 and 0.06, respectively). All these findings emphasize the usefulness of the isoniazid TDM in its dosage adjustment.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, a significant correlation would guide the clinician to prescribe a dose corresponding to the desired target concentration. This corroborates the results of a retrospective analysis performed by Moussa et al, 27 who found no correlation between isoniazid C 3 and weight dose in both patients having and patients not having adverse drug reactions ( r = 0.22 and 0.06, respectively). All these findings emphasize the usefulness of the isoniazid TDM in its dosage adjustment.…”
Section: Discussionsupporting
confidence: 92%
“…The first-line therapy for active tuberculosis consists of daily oral doses of rifampicin, isoniazid, pyrazinamide, and ethambutol, and the treatment for latent tuberculosis consists of a daily oral dose of 5 mg/kg isoniazid (or 15 mg/kg twice weekly). The plasma concentrations of isoniazid were 22-29 mM in a Moroccan population 3 h after administration of rifampicin and isoniazid in patients with active TB infections (Aït Moussa et al, 2016); in another study, the plasma isoniazid C max was between 10 and 50 mM after 6 weeks of rifampicin and isoniazid administration in patients with active TB infections (Aarnoutse et al, 2017). These concentrations in humans were measured in the systemic circulation, whereas the portal and hepatic concentrations of isoniazid would be expected to be several magnitudes higher than that in the systemic circulation and to persist for months.…”
Section: Iron Levels Modulate Human Fech Protein Levelsmentioning
confidence: 99%
“…These findings revealed that RFP could cause various types of kidney injuries. Moussa et al compared the blood concentration of RFP in patients with tuberculosis who experienced adverse events [ 31 ], and there was no difference in blood concentration. Since there may be little relationship between the dose and occurrence of adverse events, we should note decreased urine output and anuria regardless of the dose of RFP.…”
Section: Discussionmentioning
confidence: 99%